2019
DOI: 10.1101/805531
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

IL2 enhances ex-vivo expanded regulatory T cell persistence after adoptive transfer

Abstract: As regulatory T cell (Treg) adoptive therapy continues to develop clinically, there is a need to determine which immunomodulatory agents pair most compatibly with Tregs to enable persistence and stabilize suppressor function. Prior work has shown that mechanistic target of rapamycin (mTOR) inhibition can increase stability of thymic Tregs. In this study we investigated the transcriptomic signatures of ex-vivo expanded Tregs after adoptive transfer in the setting of clinically relevant immunosuppression using a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Concurrent IS therapy markedly increases the survival of adoptively-transferred autologous Tregs in the peripheral blood and LNs. Labeled autologous Tregs persist longer in monkeys given rapamycin and in greater numbers compared to nonimmunosuppressed conditions at least 50 days post-infusion (Furlan et al, 2020). Low dose IL-2 together with rapamycin further prolongs the half-life of adoptively-transferred Tregs in NHPs, with detection of labeled cells in the periphery up to 84 days after infusion.…”
Section: Tracking/monitoring Of Polyclonal or Dartregs In Normal Nhp Or Organ Allograft Recipientsmentioning
confidence: 95%
See 1 more Smart Citation
“…Concurrent IS therapy markedly increases the survival of adoptively-transferred autologous Tregs in the peripheral blood and LNs. Labeled autologous Tregs persist longer in monkeys given rapamycin and in greater numbers compared to nonimmunosuppressed conditions at least 50 days post-infusion (Furlan et al, 2020). Low dose IL-2 together with rapamycin further prolongs the half-life of adoptively-transferred Tregs in NHPs, with detection of labeled cells in the periphery up to 84 days after infusion.…”
Section: Tracking/monitoring Of Polyclonal or Dartregs In Normal Nhp Or Organ Allograft Recipientsmentioning
confidence: 95%
“…This phenomenon could potentially be alleviated by systemic IL-2 administration. Thus, Furlan et al (2020) found that, in non-transplanted monkeys, adding low dose IL-2 (1 million units/m 2 /day) to rapamycin in vivo (target trough level: 5-15 ng/ml) promoted a logarithmic increase in the halflife/persistence of adoptively-transferred, autologous NHP Treg, in effect doubling the number of stable circulating Treg compared with Treg infusion in combination with rapamycin alone. Yamada et al (2015) examined the influence of systemic IL-2 on T cell alloreactivity and the maintenance of tolerance to MHC mis-matched kidney allografts induced in cynomolgus macaques via mixed hematopoietic cell chimerism.…”
Section: Il-2mentioning
confidence: 99%
“…It subsequently declines in old age (Simon et al, 2015). Beyond the effects of these genes, patients may have several transcriptomic (Furlan et al, 2020), proteomic (Cohen Freue et al, 2013;Levitsky et al, 2013), metabolomic [reviewed in Supplementary Table S1 of McCune et al (2021a)], and lipidomic (Liggett et al, 2022) characteristics that could influence the effectiveness and toxicity of transplantation and/or sirolimus. For example, metabolomics can offer discoveries yielding new insights into how metabolites (here, endogenous, not sirolimus metabolites) influence gut physiology, organ function, and immune function (Wishart, 2019).…”
Section: Open Access Edited Bymentioning
confidence: 99%